2016
DOI: 10.1002/cbdv.201500208
|View full text |Cite
|
Sign up to set email alerts
|

Compositae Plants Differed in Leaf Cuticular Waxes between High and Low Altitudes

Abstract: We sampled eight Compositae species at high altitude (3482 m) and seven species at low altitude (220 m), analyzed the chemical compositions and contents of leaf cuticular wax, and calculated the values of average chain length (ACL), carbon preference index (CPI), dispersion (d), dispersion/weighted mean chain length (d/N), and C31 /(C31  + C29 ) (Norm31). The amounts of total wax and compositions were significantly higher at high altitude than at low altitude, except for primary alcohol, secondary alcohol, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…The Paq ratio of 0.34 can indicate for a mixture of shallow surface sediments with some green algae from the Qinghai Lake, northern Tibetan Plateau . A Norm31 value of 0.49 is similar to values calculated from leaf samples of different species of Compositae (Guo et al 2016) in differing altitudes, and also from montane plants and soils (Carr et al 2014). However, these patterns may vary with respect to local vegetation, altitude and humid or dry climate (Rao et al 2011;Zhang et al 2017), therefore, revealing more detailed palaeoenvironment information is not clearly possible.…”
Section: Surrounding Ecologysupporting
confidence: 71%
“…The Paq ratio of 0.34 can indicate for a mixture of shallow surface sediments with some green algae from the Qinghai Lake, northern Tibetan Plateau . A Norm31 value of 0.49 is similar to values calculated from leaf samples of different species of Compositae (Guo et al 2016) in differing altitudes, and also from montane plants and soils (Carr et al 2014). However, these patterns may vary with respect to local vegetation, altitude and humid or dry climate (Rao et al 2011;Zhang et al 2017), therefore, revealing more detailed palaeoenvironment information is not clearly possible.…”
Section: Surrounding Ecologysupporting
confidence: 71%
“…These results suggested that higher cuticular wax loads of S. linearistipularis leaves than those of S. matsudana leaves contributed to its higher salt tolerance. Different environmental conditions can affect the distribution and chemical composition of cuticular waxes in plants [24][25][26] . Thus, we speculated that the saline-alkali conditions affected the cuticular wax loads in S. linearistipularis leaves.…”
Section: Discussionmentioning
confidence: 99%
“…It indicated that the wax concentration was closely related to the variety. Moreover, the environmental factors such as temperature, humidity, as well as cultivation soil also were potential factors affecting the wax concentration. Pepper wax gradually accumulated with fruit development, and the S5 increased by nearly three times compared with the S1.…”
Section: Resultsmentioning
confidence: 99%